The Impact of Wage Dispersion in Football Teams Performance: An Overview of the Big-5 European Leagues of Football - Ramos, Miguel Maria Fernandes Brotas (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science